2013
DOI: 10.1002/jsfa.6308
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics profile of a naturally debittering olive in comparison to regular olive varieties

Abstract: BACKGROUND: Hurma, an olive variety that grows in a specific area in Turkey, loses its bitterness before harvesting, and therefore does not need further processing steps for the production of table olives. The total phenol content and phenolic profiles of (1) this naturally debittered olive type, Hurma; (2) the same olive variety, but not a naturally debittered type, Erkence; and (3) another variety, Gemlik, which is commonly consumed as table olive, were determined during their maturation period for two harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 17 publications
1
18
2
Order By: Relevance
“…The concentration of oleuropein decreased significantly during ripening in Erkence olives during the two seasons, which was more pronounced from the first to the 5th-7th week, which is a pattern previously described for other olive varieties (Menz and Vriesekoop, 2010;Talhaoui et al, 2015) but not in Erkence fruit (Aktas et al, 2014a).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The concentration of oleuropein decreased significantly during ripening in Erkence olives during the two seasons, which was more pronounced from the first to the 5th-7th week, which is a pattern previously described for other olive varieties (Menz and Vriesekoop, 2010;Talhaoui et al, 2015) but not in Erkence fruit (Aktas et al, 2014a).…”
Section: Resultssupporting
confidence: 82%
“…Figure 1 shows the content of oleuropein in Erkence fruit during the ripening phase on olive trees cultivated in two different locations for two seasons. First, it must be noted that previous studies reported a very much lower concentration of oleuropein in Erkence olives that the content which is depicted in Figure 1 (Arslan, 2012;Aktas et al, 2014a). In fact, the latter researchers found a higher concentration in hydroxtyrosol and apigenin than oleuropein in these olives; whereas we did not detect the presence of these substances by using HPLC-MS.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…However, more data need to be collected to reach a definite conclusion on this matter. It was hypothesised that the changes during natural debittering of olives could be related to the activities of b-glucosidase and esterase enzymes and cause a decrease in phenolic compounds (Aktas et al, 2014;Jemai et al, 2009). However, as this study shows not only phenolic compounds but also fatty acids are affected from natural debittering process since there is a separation between Erkence and Hurma olives depending on their fatty acid profiles.…”
Section: Discussionmentioning
confidence: 70%
“…Same trend was also observed in a study about Dhokar olives which are cultivated in southern region of Tunisia (Jemai et al, 2009). In addition, it was found out that Hurma olive has lower phenolic content compared to regular olive types (Aktas, Ozen, Tokatli, & Sen, 2014). Despite these studies, knowledge about natural debittering phenomenon is limited mostly to phenolic changes and further study is needed to identify the other chemical changes that take place in olive composition during maturation.…”
Section: Introductionmentioning
confidence: 99%